Psychometric properties of the Italian version of the Parent Experience of Assessment Scale - Aschieri, Filippo; Brasili, Sara; Cavallini, Anna; Cera, Giulia (Frontiers in Psychology, 2024)
This paper describes the psychometric properties of the Italian version of the Parent Experience of Assessment Scale. Overall, 185 participants participated in the study. Confirmatory factor analysis replicated the original five factors structure of the scale (Parent-Assessor Relationship and Collaboration; New Understanding of the Child; Child-Assessor Relationship; Systemic Awareness; Negative Feelings). Full scale and individual factors' reliability ranged from high to excellent. Structural equation modeling showed that Parent-Assessor Relationship and Collaboration and New Understanding of the Child factors had the strongest direct effects on parents' General Satisfaction, measured by the Client Satisfaction Questionnaire. A multivariate analysis of variance showed that the type of assessment, the children's age and the way the scale was completed impacted on the outcomes of the QUEVA-G. Results suggest that the Italian version of the Parent Experience of AssessmentScale is a valid and reliable tool for assessing parents' experience of their child's assessment.